2010
DOI: 10.1002/ddrr.117
|View full text |Cite
|
Sign up to set email alerts
|

Pain management in intellectually disabled children: Assessment, treatment, and translational research

Abstract: The primary focus of pain research in intellectually disabled individuals is still on pain assessment. Several observational pain assessment scales are available, each with its own characteristics, its own target group and its own validated use. Observational studies report differences in the treatment of intra- and postoperative pain of intellectually disabled children and almost all children with intellectual disability have comorbidities that need to be addressed. The scope of research has started to broade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 85 publications
0
16
0
4
Order By: Relevance
“…6,7 Lastly, analgesia evaluation is of primary importance in patients having communication impairment, making adequate pain relief quite impossible to provide. 19 Pupillary dilatation in response to a noxious stimulus has been well characterized. 9 -12,20,21 It is considered a reliable index of the adequacy of the analgesic component during a balanced general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Lastly, analgesia evaluation is of primary importance in patients having communication impairment, making adequate pain relief quite impossible to provide. 19 Pupillary dilatation in response to a noxious stimulus has been well characterized. 9 -12,20,21 It is considered a reliable index of the adequacy of the analgesic component during a balanced general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…5 Moreover, it has been shown that IMT-induced sedation, which could be associated with residual pain intensity, may prevent an accurate evaluation of the delivered analgesia. 6,7 Lastly, some patients, such as nonverbal or cognitively impaired patients, 8 are unable to adequately express their pain level, making IMT very difficult to implement. In these circumstances, the use of tools to provide objective evaluation of immediate postoperative analgesia and guide IMT would be of valuable help.…”
mentioning
confidence: 99%
“…Intellectually disabled children often suffer from conditions that require painful and surgical interventions (5). Several observational pain assessment tools have been developed for these patients as recently reviewed by Voepel-Lewis et al (6) and us (7). Epilepsy is also common and chronic treatment with anticonvulsants may have consequences for anesthetic and postoperative care (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Observational assessment is the only way to recognise and quantify pain in this subset of patients, and it should be performed with dedicated tools . It is well known that children with cognitive impairment suffer significantly more pain than their typically developing peers .…”
Section: Discussionmentioning
confidence: 99%